PECULIARITIES OF ACUTE APPENDICITIS IN CHILDREN - Khalilov Shukrullo Kuchkarovich (Scholar Express Journals, 2023)
Acute appendicitis is an inflammation of the cecal appendix and one of the most frequent abdominal diseases in children requiring urgent surgical intervention. The course of acute appendicitis in children is somewhat different from that in adults due to age-related peculiarities.
Keywords: Acute Appendicitis; Appendix; Cecum